Empirical study of the effects of discourse markers on the reading comprehension of Spanish students of English as a foreign language - Ana Cristina Lahuerta Martínez (International Journal of English Studies (IJES), 2009)
The aim of this work is to analyse how Spanish readers react to English discourse markers in a text. We carry out an empirical study in which we ask three research question: (a) if there is any relationship between presence of discourse markers or absence of discourse markers and reading comprehension in English as a foreign language, (b) if there is any relationship between the readers’ proficiency in English and the effect of the presence or absence of discourse markers on reading comprehension and, (c) if there is any relationship between the readers’ age, sex, competence as learners and as learners of English, and the effect of the presence or absence of discourse markers on reading comprehension. The results obtained show that discourse markers enhance reading comprehension in foreign language reading, and that the more successful students tend to use discourse markers as aids to help their reading comprehension. This latter result is nevertheless limited by the possible effect of the readers’ familiarity with the topic of the text and points to a need for further investigation.